Thyroid Function Status during Different Trimesters in Bangladeshi Women - Banik, Shyamal Chandra; Begum , Mahmuda; Ahmed , Farjana; Shamsuzzaman , Md; Saha , Kartick Chandra (Medicine Today, 2022)
Introduction: Gradual alteration of thyroid function occurs during different trimesters of gestation. Objective: To observe thyroid function status in normal pregnancy. Materials and Methods: This cross sectional study was conducted in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2016 to June 2017. The study was approved by Institutional Ethical Committee. Total 120 female subjects, age ranged from 20 to 35 years were included in this study, among them 90 were healthy pregnant women and 30 were nonpregnant women. Serum TSH, FT4 & FT3 levels were measured. The statistical analysis was done by ANOVA test and Bonferroni test. Results: In this study, mean serum TSH level was lower in 1st & 2nd trimester and higher in 3rd trimester than that of nonpregnant group. Again it was gradually higher from 1st to 3rd trimesters of gestation and the difference was statistically significant (p<0.05, p<0.001, p<0.01) in between the groups. Mean serum FT4 & FT3 levels were higher in 1st trimester and lower in 2nd & 3rd trimesters of gestation than that of nonpregnant group. Again, both these levels were gradually lower from 1st to 3rd trimesters of gestation and the difference was statistically significant (p<0.001, p<0.001, p_0.01) in between the groups. Conclusion: Gradual alterations of thyroid function status were observed during pregnancy. Serum TSH level was gradually higher and both serum FT4 & FT3 levels were gradually lower from 1st to 3rd trimesters of gestation. Medicine Today 2022 Vol.34(1): 47-50